Associations between computed tomography markers of cerebral small vessel disease and hemorrhagic transformation after intravenous thrombolysis in acute ischemic stroke patients - Zhan, Zhenxiang; Xu, Tong; Xu, Ye; Fu, Fangwang; Cheng, Zicheng; Xia, Lingfan; Wu, Yucong; Xu, Xuan; Cao, Yungang; Han, Zhao (Frontiers in Neurology, 2023)
Background Hemorrhagic transformation (HT) is common among acute ischemic stroke patients after treatment with intravenous thrombolysis (IVT). We analyzed potential relationships between markers of cerebral small vessel disease (CSVD) and HT in patients after IVT. Methods This study retrospectively analyzed computed tomography (CT) data for acute ischemic stroke patients before and after treatment with recombinant tissue plasminogen activator at a large Chinese hospital between July 2014 and June 2021. Total CSVD score were summed by individual CSVD markers including leukoaraiosis, brain atrophy and lacune. Binary regression analysis was used to explore whether CSVD markers were related to HT as the primary outcome or to symptomatic intracranial hemorrhage (sICH) as a secondary outcome. Results A total of 397 AIS patients treated with IVT were screened for inclusion in this study. Patients with missing laboratory data (n = 37) and patients treated with endovascular therapy (n = 42) were excluded. Of the 318 patients included, 54 (17.0%) developed HT within 24–36 h of IVT, and 14 (4.3%) developed sICH. HT risk was independently associated with severe brain atrophy (OR 3.14, 95%CI 1.43–6.92, P = 0.004) and severe leukoaraiosis (OR 2.41, 95%CI 1.05–5.50, P = 0.036), but not to severe lacune level (OR 0.58, 95%CI 0.23–1.45, P = 0.250). Patients with a total CSVD burden ≥1 were at higher risk of HT (OR 2.87, 95%CI 1.38–5.94, P = 0.005). However, occurrence of sICH was not predicted by CSVD markers or total CSVD burden. Conclusion In patients with acute ischemic stroke, severe leukoaraiosis, brain atrophy and total CSVD burden may be risk factors for HT after IVT. These findings may help improve efforts to mitigate or even prevent HT in vulnerable patients.